An analysis of the role of college students' core self-evaluation in the relationship between extracurricular physical exercise and academic stress - Zhu, Guanren; Cao, Wenwen; Yin, Yutong; Bai, Shengchao (Frontiers in Psychology, 2024)
Objective To explore the role of college students' core self-evaluation in the association between extracurricular physical exercise and academic stress, and to provide a reference and basis for effectively alleviating current college students' academic stress. Methods A stratified cluster random sampling method was used to conduct an online survey using the China College Student Mental Health Screening Scale, the Core Self-Esteem Scale, and a self-developed questionnaire for 1,249 college students from 8 junior colleges in Jiangsu Province, China, in January 2023, and analyses were conducted using bivariate correlation and mediation effect tests. Results More than half of the students were worried about lagging behind other students in their studies and worrying about exams, as well as more than half of the students had <2 h of extracurricular physical exercise per week in terms of academic stress. Significant correlations were found between extracurricular physical exercise time and core self-evaluation (r = 0.225, p < 0.01), academic stress (r = −0.317, p < 0.01), and between core self-evaluation and academic stress (r =−0.371, p < 0.01). Extracurricular physical exercise had a negative predictive effect on academic stress (effect = −0.306, 95%CI: −0.361 -0.251) and partially through the mediating path of core self-evaluation, (effect = −0.067, 95%CI: −0.091 -0.046), with a mediating effect of 21.9%. Among them, the mediating effect of core self-evaluation was highest in “worrying about lagging behind other students in their studies” and “worrying about exams”, which accounted for 24.4% and 24.3% respectively. Conclusion Currently, college students have different degrees of academic stress; extracurricular physical exercise can reduce academic stress through direct effects, and also through the indirect effect of improving the level of core self-evaluation, and active extracurricular physical exercise has become an important way to promote students' physical and mental health.